Vibrancy of public spaces. Inclusivity and participation amidst the challenges in transformative process in the city of Cagayan de Oro, Philippines. - Satur, Luzile (regiospectra, 2020)
Vibrancy of Public Spaces examines the dynamics which lead to revitalization of everyday life in the public spaces of the City of Cagayan de Oro in Northern Mindanao, Philippines. By employing oriental philosophies together with western thoughts, this study elucidates that the core of perceived, lived and conceived spaces is ‘the Subject’. Once the Subject utilizes the public sphere to instill social action, social space is ultimately produced. Hawkers, grassroots environmental activists, street readers and artists are the social Subjects who partake in the vibrancy of public spaces. The social Subjects utilize public spaces as venues of social transformation. Grassroots environmental activists together with the urban poor demanded for environmental justice in the aftermath of typhoon Washi (Sendong). The Night Café hawkers in the plaza of Divisoria strengthened the informal economy through generation of employment and livelihood. Street tutors and performers take on the roles as educators and artists in the reduction of dehumanized individuals in public spaces amidst the violent operations against possession of abused substance. Therefore, the social Subjects’ role in democratic process lead to inclusivity of the marginalized sector in the public spaces of the city.
Lebendigkeit des öffentlichen Raums. Inklusivität und Partizipation inmitten der Herausforderungen des transformativen Prozesses in der Stadt Cagayan de Oro, Philippinen.
Keywords: Öffentlicher Raum; Stadtleben; Revitalisierung; Nutzungsvielfalt; Öffentlichkeit; Inklusion; Partizipation; Stadtraum; Stadtbewohner; Freiraumkonzept; Stadtsoziologie; Stadtwachstum